The emergence of sociological theory - Turner, Jonathan H.; Beeghley, Leonard; Powers, Charles H.; Turner, Jonathan H. (SAGE, 2012)
A comprehensive exploration of classical social theory portraying the historical context (Renaissance Europe to the Industrial Age), covering all major developments in sociological theory (the Enlightenment to George Herbert Mead) and focusing on all the key figures you would expect: Comte, Spencer, Marx, Weber, Simmel, Durkheim and Mead